Abscess formation caused by a foreign body reaction to a poly-D, L-lactic acid (PDLLA) absorbable plate for zygomaticomaxillary complex (ZMC) fracture - Fumikazu Tamura (2023)
The poly-D, L-lactic acid absorbable plate does not contain poly L-lactic acid, which is the main factor in foreign body reactions; therefore, with use of this plate, a foreign body reaction is unlikely. In fact, few reports have been published on removal of a poly-D, L-lactic acid absorbable plate owing to a foreign body reaction.